Placebo and nocebo in clinical practice: An online cross-sectional survey of healthcare professionals from European countries on views, practices and training needs - Mary O’Keeffe; Nathan Skidmore; Arianna Bagnis; Przemysław Bąbel; Elżbieta A. Bajcar; Alessandra De Palma; Andrea W.M. Evers; Eveliina Glogan; Julia W. Haas; Stefanie H. Meeuwis; Marek Oleszczyk; Antonio Portolés; et al. (PLoS ONE, 2026)
Background Placebo and nocebo effects significantly influence health outcomes, yet healthcare professionals receive limited training and guidance on their mechanisms and clinical application, creating a gap in education and practical understanding. Conducted within the European PANACEA Consortium, this study evaluated healthcare professionals’ knowledge, attitudes, and practices regarding placebo and nocebo effects, and assessed their needs in further education. Methods An online cross-sectional survey among a European multi-country convenience sample of healthcare professionals collected data assessing participants’ knowledge, perceptions, and experiences regarding placebo and nocebo effects; their application and ethical considerations in clinical practice; and investigated educational needs and interest in further training. Quantitative data were analyzed using descriptive statistics, and thematic analysis was applied to the free-text responses. Results Amongst 807 participants, 71.7% reported taking advantage of placebo effects in their practice, and over half of participants (55.8%) observing nocebo effects. Participants reported feeling somewhat confident (53.3%) in harnessing placebo effects with 47.5% feeling confident in preventing nocebo effects. The majority of respondents had not received formal training on placebo and nocebo effects, with most expressing an interest in further training in areas such as healthcare education, emphasizing communication skills to enhance placebo effects, and knowledge to recognize and reduce nocebo effects. Conclusions There is a significant need for more comprehensive training on placebo and nocebo effects, particularly in early health professional education. These findings informed the development of educational resources and best practice recommendations developed as part of the outcomes from the PANACEA Consortium, improving the understanding and application of these effects among healthcare professionals across Europe.